EFFECT OF NATURAL IRON OXIDE, HYDROGEN PEROXIDE, AND OXALIC ACID ON PHOTOCHEMICAL DEGRADATION OF 2-CHLOROPHENOL (Sciences & Technology. A, exactes sciences, 2014)
The voluntary or accidental release of chemical compounds in the environment is a major cause of pollution of natural waters. Most of chlorophenols are toxic and hardly biodegradable and are difficult to remove from the environment. Therefore, it is important to ﬁnd innovative and economical methods for the safe and complete destruction. The objective of this work is to test the activity photocatalytic of natural iron oxide (NIO) in the photodegradation of 2-chlorophenol (2-CP). The analysis chromatographic with HPLC of solutions exposed under UV irradiation revealed that the degradation of 2-CP was negligible under the condition of using only natural iron oxide. The effect of wavelength on photoreactivity of NIO was also investigated in this process: at high wavelength thus at low energy the efficiency of degradation is important. We have also investigated the activation of NIO by hydrogen peroxide and oxalic acid, The results showed that the photodegradation of 2-CP under UVA irradiation could be enhanced greatly in the presence of oxalate. 2-CP was completly removed after 240 minutes of irradiation when the concentration of oxalic acid is equal to 2.10-3 M. The use of 2.0 % of isopropanol as a scavenger confirmed the intervention of hydroxyl radicals in the photodegradation of 2-CP.